To Preserve or To Perfect? Rousseau’s Take on Hygiene - Le Menthéour, Rudy (Sens public)

(untitled) (Département des littératures de langue française, 2019)
Hygiene has been constantly undervalued in Rousseau’s work. This article considers the reasons that led to such a dismissal and reevaluates hygiene as a major source of inspiration for Rousseau. Such a reevaluation implies rehabilitating hygiene as an ever-expanding subfield in 18th-Century France. If Rousseau borrowed many concepts and approaches to hygiene, hygienists accepted in return Rousseau as one of their own. Reexamining Rousseau’s take on hygiene has major implications on the way one conceives the evolution of hygiene over the course of the 18th and the 19th centuries: his approach did not lead toward “public hygiene,” but toward what might be better defined as “political hygiene.” By reappraising Rousseau’s contribution, we will be better equipped to avoid a teleological conception of hygiene.